Managing Diamide Resistance in Florida Tomato - Hugh A. Smith (EDIS)
As with any insecticide, repeated use of diamide insecticides on successive generations of the same pest may lead to the development of insecticide resistance. In order to avoid the development of resistance to diamides by targeted pests of tomato, group 28 insecticides, including diamides, must be rotated with insecticides possessing different modes of action. This 3-page fact sheet was written by Hugh A. Smith, and published by the UF Department of Entomology and Nematology, February 2013.